Diabetic neuropathy: Past, present, and future - Juan Quiroz-Aldave; María Durand-Vásquez; Elman Gamarra-Osorio; Jacsel Suárez-Rojas; Pela Jantine Roseboom; Rosa Alcalá-Mendoza; Julia Coronado-Arroyo; Francisca Zavaleta-Gutiérrez; Luis Concepción-Urteaga; Marcio Concepción-Zavaleta (Babol University of Medical Sciences, 2023)
Background: A sedentary lifestyle and an unhealthy diet have considerably increased the incidence of diabetes mellitus worldwide in recent decades, which has generated a high rate of associated chronic complications. Methods: A narrative review was performed in MEDLINE, EMBASES and SciELO databases, including 162 articles. Results: Diabetic neuropathy (DN) is the most common of these complications, mainly producing two types of involvement: sensorimotor neuropathy, whose most common form is symmetric distal polyneuropathy, and autonomic neuropathies, affecting the cardiovascular, gastrointestinal, and urogenital system. Although hyperglycemia is the main metabolic alteration involved in its genesis, the presents of obesity, dyslipidemia, arterial hypertension, and smoking, play an additional role in its appearance. In the pathophysiology, three main phenomena stand out: oxidative stress, the formation of advanced glycosylation end-products, and microvasculature damage. Diagnosis is clinical, and it is recommended to use a 10 g monofilament and a 128 Hz tuning fork as screening tools. Glycemic control and non-pharmacological interventions constitute the mainstay of DN treatment, although there are currently investigations in antioxidant therapies, in addition to pain management. Conclusions: Diabetes mellitus causes damage to peripheral nerves, being the most common form of this, distal symmetric polyneuropathy. Control of glycemia and comorbidities contribute to prevent, postpone, and reduce its severity. Pharmacological interventions are intended to relieve pain.